DESIGN SIMULATION TO PASS TESTS FOR ACCEPTANCE AS DEFINED IN PREN 14363 OR UIC518 - Fisher, B.; Menssen, R.; Markova, O.; Kovtun, H. (Science and Transport Progress, 2005)
It is necessary to investigate the behavior of the rail crew using computer simulations to be sure that the newly designed and developed rail crew successfully pass the acceptance tests. The evaluation of the effect of changes of various parameters allows optimising the dimensions and design parameters.In the work the necessary simulation options for the evaluation of the dynamic characteristics of crew are described in details. It is shown what parameters determine the accuracy of the solution of the task.